2018
DOI: 10.1186/s12885-018-4137-8
|View full text |Cite
|
Sign up to set email alerts
|

Centralising specialist cancer surgery services in England: survey of factors that matter to patients and carers and health professionals

Abstract: This study examines and ranks factors important to patients and carers, and health care professionals in order to inform the implementation of centralisation of specialist cancer surgical services. The most important factors were similar in the two stakeholder sub-groups. Planners should consider the impact of reorganising services on these factors, and disseminate this information to patients, the public and health care professionals when deciding whether or not and how to centralise specialist cancer surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…15,16 Although there often seems to be resistance to the process of centralisation, 9 it appears that its acceptability to patients, particularly as far as the need to travel for both outpatient evaluation and inpatient care is concerned, is outweighed by the perceived clinical benefit. 17 19 Therefore, the distance between tertiary or quartenary centres is not a major factor that inhibits the adoption of regional or supra-regional network structures.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Although there often seems to be resistance to the process of centralisation, 9 it appears that its acceptability to patients, particularly as far as the need to travel for both outpatient evaluation and inpatient care is concerned, is outweighed by the perceived clinical benefit. 17 19 Therefore, the distance between tertiary or quartenary centres is not a major factor that inhibits the adoption of regional or supra-regional network structures.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into patient preferences have revealed that patients with cancer are willing to travel to access specialized surgical care and improve their outcome. However, if there is no increased risk of complications or death, patients prefer to be cared for locally, closer to home, as this often allows for reduced patient‐incurred costs and increased social support from family and friends.…”
Section: Discussionmentioning
confidence: 99%
“…The study highlights the ability to obtain similar survival for patients by combining surgery for pancreatic adenocarcinoma in specialized centres with decentralized administration of adjuvant chemotherapy, closer to home. This is crucial information for designing patient‐centred and sustainable healthcare delivery strategies and networks of cancer care that support patients to be cared for close to their homes while being offered optimal cancer outcome, along with better social support, enhanced experience and reduced travelling and financial burdens , .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study therefore aimed to explore consultants’ views on perceived benefits of, and barriers to, implementing a centralized skin lesion unit, alongside potential settings, multidisciplinary team working and private sector involvement. These are factors of importance identified in research regarding centralization of other specialties . A qualitative research methodology was chosen in order to generate rich data and allow detailed explication of participants’ views.…”
mentioning
confidence: 99%